Feeling safe: a critical look at the effect of neighborhood safety features and perceptions on childhood symptoms of depression - Erika Infantino; Tracie A. Barnett; Carolyn Côté-Lussier; Andraea Van Hulst; Mélanie Henderson; Marie-Eve Mathieu; Catherine Sabiston; Lisa Kakinami (BMC Pediatrics)
Abstract Background Physical characteristics and perceptions of an environment can have enduring effects on one’s mental health. The present study aimed to determine whether a set of measures of neighborhood safety – independent built environment features, parents’ perception of neighborhood safety and community cohesion, and children’s perception of neighborhood safety – best related to symptoms of depression in young boys and girls from Montréal, Québec. Methods Data were from the Quebec Adipose and Lifestyle Investigation in Youth (QUALITY) cohort. Participants were aged 8 to 10 years (M = 9.5) at baseline (2005). Measures included: child symptoms of depression, neighborhood perception (child and parentally reported), and independent rater assessed visible disorder/neighborhood safety issues and road safety features. Multiple linear regressions were used to examine the relation between neighborhood safety measures and symptoms of depression for boys (n = 262) and girls (n = 212) at baseline and at follow-up time approximately 2 years later in 2008 after adjusting for baseline sex, age, body mass index, pubertal status, physical activity, family income, parent education, population density, and land-use mix. Analyses were sex stratified. Results Greater child perceived safety was associated with lower symptoms of depression in boys at both baseline and follow-up, and greater community cohesion was associated with lower symptoms of depression in girls at baseline. These results were not maintained after adjusting for multiple testing. Conclusion Future research should elucidate the more precise pathways linking neighborhood safety to symptoms of depression among children and consider differences across sexes.